Context-dependency of monarch butterfly (Danaus plexippus) egg abundance on milkweeds (Asclepias) - Katie Harris; Timothy M. Reinbott; Terry Woods; Jared M. Brabant; Grant Harris; Deborah L. Finke (PLoS ONE, 2025)
North American monarch ( Danaus plexippus ) populations have experienced sharp declines. Loss of milkweed is among the major drivers of this decline. Our objective is to identify factors that influence milkweed habitat quality for monarchs to inform habitat reconstruction efforts. We measured the response of monarch egg abundance to milkweed patch characteristics (milkweed species identity and co-occurring insects) and features of the surrounding landscape (wildflower nectar plants and land use context). From May through September 2019 and 2021, we assessed the abundance of naturally occurring monarch eggs, lady beetles (predators), and aphids (competitors) on swamp milkweed ( Asclepias incarnata ) and common milkweed ( A. syriaca ) plants established in a diverse matrix of wildflower nectar plants or monoculture of fescue grass and located in open row crop habitats or abutting wooded edges. We found that local patch characteristics had the largest effects on monarch egg abundance. Egg abundance differed across milkweed species, but the milkweed species with the highest monarch egg abundance switched from common milkweed in 2019 to swamp milkweed in 2021. We also found that monarch egg abundance was positively associated with oleander aphid ( Aphis nerii ) abundance on both milkweed species, despite significantly higher aphid abundance on swamp milkweed than common milkweed. Lady beetles exhibited a numerical response to oleander aphid prey, but there was no evidence that greater numbers of these generalist predators negatively affected monarch eggs. Landscape features also influenced monarch egg abundance, but the effects varied across milkweed species and years. In 2019, egg abundance was higher on swamp milkweed near trees than in open crop fields, while proximity to wildflower nectar plants increased egg abundance on common milkweed; landscape features did not directly affect egg abundance in 2021. Our results highlight the important role of environmental context in mediating the conservation value of milkweed plantings for monarchs.